Análisis socioeconómico e incidencia del comercio informal a los comerciantes del mercado cerrado del cantón Latacunga durante el periodo 2014-2015 - Casa Iza, Mónica Alexandra (2015)
The main objective of this research is based on present economic reality of the formal market traders closed Latacunga, how and to what extent informal vendors affect this sector of the economy. Note that the choice of this theme was given by the growing presence of street vendors in Latacunga, located on the sidewalks of the central portion thereof, a situation that makes the beauty of this city is overshadowed, this despite the great efforts made by the authorities for the construction of closed market, which hosted the vast majority of people in the square selling Falls in pretty deplorable conditions….